INNOVATIVE APPROACHES IN THE FORMATION NEW CONCEPTS UNDER LEARNING SUBJECT ELECTRICAL ENGINEERING - Анисимов, Николай (SWorldJournal, 2022)
The article discusses new approaches and principles of teaching one of the technical disciplines, namely "Electrical Engineering". It should be noted that this discipline is taught in 76% of all types of educational institutions. The theoretical significa